A monetary Keynesian view of modern monetary theory - Sebastian Dullien; Silke Tober (European Journal of Economics and Economic Policies: Intervention (EJEEP), 2022)
Both monetary Keynesian theory and modern monetary theory (MMT) place money at the center of the analysis and highlight the important economic role of the state in a monetary market economy in which full employment is neither the norm nor the center of gravity. Whereas monetary Keynesian theory implies that economic policy is considerably constrained by market forces, MMT considers economic policy to be all-powerful and able to ensure full employment. Polarizing MMT policy conclusions such as the proposition that modern states have no budget constraint result from MMT-ers' neglect of crucial elements of the Keynesian framework. As Hajo Riese tirelessly argued, monetary financing of budget deficits has limits even in the presence of unemployment because the stability of a monetary market economy hinges on the scarcity of its money.
Keywords: 330; modern monetary theory; budget deficits; monetary financing; fiscal policyE42; E50; E63; B52